2023
DOI: 10.1002/smll.202304988
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitance‐Induced Synaptic Plasticity of Tribo‐Phototronic Effect Between Ionic Liquid and 2D MoS2

Ribwar Ahmadi,
Amin Abnavi,
Amirhossein Hasani
et al.

Abstract: Contact‐induced electrification, commonly referred to as triboelectrification, is the subject of extensive investigation at liquid–solid interfaces due to its wide range of applications in electrochemistry, energy harvesting, and sensors. This study examines the triboelectric between an ionic liquid and 2D MoS2 under light illumination. Notably, when a liquid droplet slides across the MoS2 surface, an increase in the generated current and voltage is observed in the forward direction, while a decrease is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…We have also previously reported that the water-MoS 2 device demonstrates a reflectance of ≈3.5% at the same wavelength. [36] Therefore, the absorption of water is minimal at this specific wavelength. MoS 2 on its own is not a polarization-sensitive material due to its isotropic structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also previously reported that the water-MoS 2 device demonstrates a reflectance of ≈3.5% at the same wavelength. [36] Therefore, the absorption of water is minimal at this specific wavelength. MoS 2 on its own is not a polarization-sensitive material due to its isotropic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Although MoS 2 is typically an n-type semiconductor, the IV characteristics and band bending of MoS 2 -water heterojunction are similar to those of p-type silicon-water probably due to the low electron concentration of MoS 2 . [36] Upon white light illumination (solar spectrum, AM1.5G) at an intensity of 100 mW cm −2 , the concentration of photogenerated carriers in the MoS 2 increases, leading to an increase in the photogenerated current density of the MoS 2 -water device and an open circuit voltage of ≈0.52 V, demonstrating the photovoltaic effect [37] (Figure 1e). To study the pyroelectric behavior of the MoS 2 -water junction, a series of heat pulses at temperatures of ≈40, 60, 80, and 100 °C were applied to the backside of the MoS 2 -water device (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…As solid-liquid contact electrication (S-L CE) is the rst step of CEC, the discussion of CE is the direct way to rst reveal the mechanism of CEC. S-L CE includes S-L electron transfer and S-L ion transfer, 21,22 where the former is the process of producing electron-hole pairs to generate ROS through the mass transfer process of electrons in the CEC reaction, 23 whereas the latter has a weak contribution to CEC performance. 24 Under natural or industrial conditions, the water composition is complicated.…”
Section: Introductionmentioning
confidence: 99%